Infiltration of LPAR5+ macrophages in osteosarcoma tumor microenvironment predicts better outcomes - He, Yi; Zhou, Haiting; Huang, Xiaojian; Qu, Yunkun; Wang, Yingguang; Pei, Wenbin; Zhang, Rui; Chen, Sheng; You, Hongbo (Frontiers in Immunology, 2022)
Tumor microenvironment (TME) has been shown to be extensively involved in tumor development. However, the dynamic change of TME components and their effects are still unclear. Here, we attempted to identify TME-related genes that could help predict survival and may be potential therapeutic targets. Through ESTIMATE algorithm, we found that immune score, stromal score and ESTIMATE score were all highly correlated with overall survival, indicating that the proportion of immune and stromal components was an important prognostic factor. Then we screened out the key gene, LPAR5, by differential analysis and Cox regression analysis. Subsequently, we found that LPAR5 was highly correlated with prognosis and metastasis. And the expression of LPAR5 was positively correlated with immune cells, especially macrophages, by immune infiltration analysis, single cell RNAseq analysis and immunofluorescence staining, indicating LPAR5+ macrophages played an important role in tumor microenvironment of osteosarcoma. GSEA analysis also showed that the genes in LPAR5 high expression group were enriched in immune-related activities and pathways, and differentially expressed genes between LPAR5+ macrophages and LPAR5- macrophages were enriched in the biological processes associated with phagocytosis and antigen presentation. The result of GEO datasets further demonstrated that LPAR5 expression was higher in tumor tissues than in normal tissues and osteosarcoma cell lines, which supporting our finding that LPAR5 was mainly expressed in TME. And high LPAR5 expression predicting a better prognosis was also verified by GEO datasets and immunohistochemical staining. In conclusion, we identified a TME-related gene, LPAR5, which is a promising indicator for TME remodeling in osteosarcoma. Particularly, LPAR5+ macrophages might have great potential to be a prognostic factor and therapeutic target for osteosarcoma.